Armies of Pestilence: CNS Infections as Potential Weapons of Mass Destruction - Hart, B.L.; Ketai, L. (American Journal of Neuroradiology, 2015)
SUMMARY: Infectious agents have been investigated, developed, and used by both governments and terrorist groups as weapons of mass destruction. CNS infections, though traditionally considered less often than respiratory diseases in this scenario, may be very important. Viruses responsible for encephalitides can be highly infectious in aerosol form. CNS involvement in anthrax is ominous but should change treatment. Brucellosis, plague, Q fever, and other bacteria can uncommonly manifest with meningoencephalitis and other findings. Emerging diseases may also pose threats. We review infectious agents of particular concern for purposes of biowarfare with respect to CNS manifestations and imaging features.